Pengaruh Model Pembelajaran Flipped Classroom Terhadap Hasil Belajar Materi IPAS Bab II Topik B Kelas IV Di UPTD SDN Keleyan I Bangkalan - Sandro Jadi Marulitua Nadeak; Priyono Tri Febrianto (Universitas Maritim AMNI Semarang, 2023)
This type of research is Pre-Experiment Design research which aims to determine the effect of implementing the flipped class learning model on the learning outcomes of IPAS CHAPTER II Topic B in class IV UPTD SDN Keleyan 1 Bangkalan and the sample consists of one class IV UPTD SDN Keleyan 1 which was selected using techniques purposive sampling. The data collected consists of data on student learning outcomes. The data collection technique used is a test, where the test consists of 10 pretest and posttest multiple choice questions with data processing techniques of normality test, homogeneity test, and hypothesis test using the SPSS program version 25. The research results show that There is a positive and significant influence of the flipped class learning model with the help of YouTube, Viedo and teacher learning media on the learning outcomes of. This can be seen from the numbers obtained from the pretest observation scores of 45% complete and 50% incomplete before treatment was given. Meanwhile, after being given treatment in the very good category, 36% completed, and 63% did not complete and experienced a change in category in the very good posttest, as much as 68% included completeness of student learning outcomes.